Metformin for Preventing Type 2 Diabetes Mellitus in Women with a Previous Diagnosis of Gestational Diabetes: A Narrative Review - Versace, Vincent L.; Beks, Hannah; Wesley, Hannah; McNamara, Kevin; Hague, William; Anjana, Ranjit Mohan; Mohan, Viswanathan; Khunti, Kamlesh; Dunbar, James A. (Seminars in Reproductive Medicine, 2020)
Women with a history of gestational diabetes mellitus (GDM) are at greater risk of developing type 2 diabetes mellitus (T2DM) when compared with women who have not had GDM. To delay or prevent T2DM, guidelines recommend regular screening in the primary care setting and lifestyle interventions that are largely focused on dietary and physical activity modifications. As the postpartum period can be challenging for women, uptake and engagement in screening and lifestyle interventions have been poor. Poor uptake and engagement places women with a history of GDM at heightened risk for future morbidity and development of T2DM. Metformin has been a longstanding and safe treatment for the control of blood glucose in people with T2DM. Research has supported the efficacy of metformin, used as an adjunct to a lifestyle intervention or as a stand-alone treatment, in preventing T2DM in people at high risk of T2DM. Findings from longitudinal studies have demonstrated the potential for metformin to reduce conversion to T2DM when used by women with a previous diagnosis of GDM. This review examines the potential effectiveness of metformin to reduce the incidence of T2DM among women with a previous diagnosis of GDM in the “real-world” setting.
Keywords: gestational diabetes; type 2 diabetes mellitus; risk factors; preventive medicine; metformin